Validation of sanitizer efficacy in commercial apple dump tanks using a Listeria monocytogenes surrogate - Yuan Su; Mengqian Hang; Xiaoye Shen; Zi Hua; To Chiu; Jeanene M. Deavila; Qi Sun; Bhim B. Thapa; Edmund L. Afari; Yiqing Du; Stuart Goatley; Manoella Mendoza; et al. (Food Microbiology, 2026)

Listeria survival dynamics on pears under real-world storage: effects of variety, production practice, storage, and decay - Edmund Larbi Afari; Mengqian Hang; Yuan Su; Xiaoye Shen; Zi Hua; Bhim Thapa; Moonbin Jo; Jeanene M. Deavilla; Xun Zhang; Manoella Mendoza; To Chiu; Rob Blakey; et al. (Food Microbiology, 2026)

Microbiota and free amino acid dynamics during aging of Cougar Gold cheese: insights into the puffy defects - To Chiu; Bing Han; Alejandro Bravo Iniguez; Mei-Jun Zhu (International Journal of Food Microbiology, 2026)

Evaluating serotype-specific survival of Listeria monocytogenes and Listeria innocua on wax-coated Granny Smith apples during storage - Xiaoye Shen; Yuan Su; Zi Hua; To Chiu; Yuanhao Wang; Manoella Mendoza; Ines Hanrahan; Mei-Jun Zhu (International Journal of Food Microbiology, 2025)

Detection and tracing of Paucilactobacillus wasatchensis from dairy farm to creamery using N-acetyltransferase (NAT) gene-derived primers - To Chiu; Tonia Green; Mei-Jun Zhu (International Dairy Journal, 2023)

Fate of Listeria innocua on wax-coated Fuji apple surfaces under commercial refrigerated air storage - Yuan Su; Xiaoye Shen; Zi Hua; Hongmei Zhu; To Chiu; Yuanhao Wang; Manoella Mendoza; Ines Hanrahan; Mei-Jun Zhu (Postharvest Biology and Technology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)